An Analysis of Metaphors in The Album “The Black Parade” My Chemical Romance - Regita, Ardea; Wibowo, Hanafi (International Journal of Education, Information Technology, and Others, 2024)
This study examines the use of metaphors in the album The Black Parade by My Chemical Romance, focusing on the types and functions of metaphors to understand the deeper meanings conveyed through the lyrics. Using Lakoff and Johnson’s Conceptual Metaphor Theory, the research identifies and classifies metaphors in the album's lyrics into ontological, structural, and orientational categories. The study finds that metaphors play a significant role in evoking emotional responses, articulating philosophical themes, and critiquing societal norms. Additionally, the study highlights ten functional roles of metaphor, including expressive, aesthetic, cognitive, and heuristic functions, which contribute to the songs' complex narrative and emotional impact. By exploring these metaphorical expressions, the research reveals how the album addresses themes of life, death, identity, and rebellion, making it not only a musical work but also a profound commentary on existential struggles. This analysis enhances understanding of figurative language in music, offering insight into how metaphors communicate intricate ideas in accessible and relatable ways